Jaringan Sosial Kelompok Usaha Pengolahan Ikan Asin Sepakat Dalam Program Pemberdayaan Perempuan di Gampong Pulau Kayu Kecamatan Susoh Kabupaten Aceh Barat Daya - Chaniago, Zul Hendri (Universitas Teuku Umar, 2024)
The objective of this study was to elucidate the role of social networks within the Sepakat women's business group in the women's empowerment program in Gampong Pulau Kayu, Susoh District, Southwest Aceh District. This program aims to empower women through the processing of raw fish into salted fish. A descriptive qualitative approach was employed, utilizing purposive sampling to select informants who possess understanding, knowledge, and involvement in the Sepakat women's business group. The analysis of this study was based on the concept of social networks, examining social relationships encompassing interest networks, emotional networks, and power networks. The findings revealed a stronger social network within the salted fish processing business group, particularly in the form of emotional networks. These emotional networks were characterized by homogeneity, with members sharing the same religion and ethnicity. This homogeneity positively impacted the group by facilitating faster information dissemination among members, fostering a high level of trust, ensuring smooth implementation of salted fish processing, and establishing harmonious cooperation among groups.